The Effect of Servant Leadership on Employee Performance Through Burnout at PT BPJS Ketenagakerjaan Karimunjawa Branch Office - Rafli Ihza Rizaldi; Anang Kistyanto (Social Science Studies, 2022)
The purpose of this study was to investigate and analyze the effect of servant leadership on employee performance through burnout on BPJS Ketenagakerjaan Kantor Cabang Surabaya Karimunjawa. Respondents to this study are as many as 34 enployee participated through a purposive non-probality sampling technique. Statistical analysis used in this study is Partial Least Square (PLS) with the help of smartPLS 3.0 software. The results showed that servant leadership has a positive and significant effect on employee performance. Servant leadership has a negative and significant effect on burnout and burnout had no significant effect on employee performance. Results also indicate thar burnout does not mediate the effect servant leadership on employee performance.